Formação ética em cursos superiores da Computação: uma perspectiva para a promoção de agentes morais responsáveis - Silva, Roberto Cardoso Freire da (2024)
The popularization of the Internet and recent innovations in the field of computing, specifically regarding Big Data and Artificial Intelligence (AI), present challenges for Education. Parts of our lives and interactions in digital environments are being developed in settings controlled and managed by algorithms that reconfigure based on our actions, limiting our choices, influencing our worldviews, and shaping how we are socially represented, both within and outside virtual environments. A significant challenge is the ethical-moral education of undergraduates who work directly in the production of these data-driven technologies. Although the National Curriculum Guidelines (DCN) for Computing courses recommend the development of "ethical, social, legal, and economic issues" as an integral and fundamental part of the training process, the education of these responsible moral agents has been little studied in the field. This thesis presents a perspective for the ethical education of these professionals after an empirical and documentary investigation involving five higher education Computing courses, both public and private, from four regions of Brazil, as well as a North American university renowned for innovation. The data were produced from interviews with course coordinators and the study of their Pedagogical Projects. The research was developed under a qualitative approach guided by the critical-transformative paradigm and utilized content analysis. The theoretical framework includes authors aligned with a problematizing perspective on education, such as Freire, Arendt, Goergen, and those discussing ethics and moral education from a non-prescriptive historical perspective, like Goergen, Vázquez, Oliveira, and Cortella. Our analysis indicates the inadequacy of traditional approaches to ethical education in Computing, characterized by the occasional offering of topics in isolated subjects and the superficial and decontextualized transmission of "universal values". This approach contributes little to the formation of morally conscious agents critically aware of the implications of their practices. Indeed, these professionals are often subjected to training processes that prioritize market values, distorting ethical principles in favor of economic interests. To address this challenge, it is urgent to revisit and restructure policies, assumptions, and educational practices in the field of Computing. This work highlights the need for adjustments in the National Curriculum Guidelines (DCN) to support a reformulation of the Pedagogical Projects of Courses (PPC) that embrace a dialogical transdisciplinarity, representative of different subjects in their fields of knowledge, ensuring that the collective's representative social values permeate and guide the entire training process. As normative mechanisms representing the public interest, the DCN must create conditions for training spaces not to be co-opted by market or specific group interests, which are contrary to citizen education.